2018
DOI: 10.1007/978-3-319-93485-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells Reveal Common Neurodevelopmental Genome Deprograming in Schizophrenia

Abstract: Schizophrenia is a neurodevelopmental disorder characterized by complex aberrations in the structure, wiring, and chemistry of multiple neuronal systems. The abnormal developmental trajectory of the brain is established during gestation, long before clinical manifestation of the disease. Over 200 genes and even greater numbers of single nucleotide polymorphisms and copy number variations have been linked with schizophrenia. How does altered function of such a variety of genes lead to schizophrenia? We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…In all conditions that led to cortical underdevelopment (SZ, C+TNF, SZ+TNF), the paucity of the cell bodies was accompanied by increased spaces between cells that were ''vacant'' in C+TNF but became filled with the ECM fibrous material in SZ and in SZ+TNF organoids. This suggests that SZ promotes ECM development, consistent with the presence of ECM regulating genes within the SZ dysregulated transcriptome (Narla et al, 2018). Such changes may alter the mechanical properties (surface tension) of the developing cortex, which could further influence the development of the brain cortex (Kroenke and Bayly, 2018) and, potentially, lead to mild cerebral atrophy observed in SZ patients (Weinberger et al, 1979).…”
Section: Sz and Tnf Change Microstructure Of The Organoid Cortexmentioning
confidence: 59%
See 4 more Smart Citations
“…In all conditions that led to cortical underdevelopment (SZ, C+TNF, SZ+TNF), the paucity of the cell bodies was accompanied by increased spaces between cells that were ''vacant'' in C+TNF but became filled with the ECM fibrous material in SZ and in SZ+TNF organoids. This suggests that SZ promotes ECM development, consistent with the presence of ECM regulating genes within the SZ dysregulated transcriptome (Narla et al, 2018). Such changes may alter the mechanical properties (surface tension) of the developing cortex, which could further influence the development of the brain cortex (Kroenke and Bayly, 2018) and, potentially, lead to mild cerebral atrophy observed in SZ patients (Weinberger et al, 1979).…”
Section: Sz and Tnf Change Microstructure Of The Organoid Cortexmentioning
confidence: 59%
“…The study by Narla et al ( 2017 , 2018 ) identified genes dysregulated in SZ NPC as belonging to the general Gene Ontology categories of neuronal development (overexpressed genes) and oligodendrogenesis (underexpressed genes). The exemplary genes of these two categories were found to be affected by nFGFR1: stimulated (neuronal genes: TH, DISC1, Wnt7B, NeuroD) and inhibited (oligodendrocytic genes: Olig 2, Olig 1; Narla et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations